Problematic Internet use in Chinese adolescents and its relation to psychosomatic symptoms and life satisfaction - Sun Ying; Cao Hui; Wan Yuhui; Hao Jiahu; Tao Fangbiao (BMC, 2011)
Abstract Background Problematic Internet use (PIU) is a growing problem in Chinese adolescents. Little is known about associations of PIU with physical and psychological health. This study was designed to investigate the prevalence of PIU and to test the relationships between PIU and psychosomatic symptoms and life satisfaction among adolescents in mainland China. Methods A cross-sectional survey was conducted comprising a large representative sample of 17 599 students in eight cities of China. PIU was assessed by the 20-item Young Internet Addiction Test (YIAT). The Multidimensional Sub-health Questionnaire of Adolescents and the Multidimensional Students' Life Satisfaction Scale were administered to obtain information on psychosomatic symptoms and life satisfaction. Demographics and Internet usage patterns were also collected. Logistic regression was used to assess the effects of PIU on psychosomatic symptoms and life satisfaction. Results Approximately 8.1% of subjects showed PIU. Adolescents with PIU were associated with males, high school students, urban, eastern and western areas, upper self-report family economy, service type mostly used for entertainment and relieving loneliness and more frequency of Internet use. Compared with normal Internet users, adolescents with PIU were more likely to suffer from psychosomatic symptoms (P < 0.001), including lack of physical energy (P < 0.001), physiological dysfunction (P < 0.001), weakened immunity (P < 0.001), emotional symptoms (P < 0.001), behavioural symptoms (P < 0.001) and social adaptation problems (P < 0.001). Adolescents with PIU had lower scores on total and all dimensions of life satisfaction (all P < 0.001). Adjusted for the demographic and Internet-related factors, there was positive significant relationship between PIU and psychosomatic symptoms, but negatively related to life satisfaction. Conclusions PIU is common among Chinese students, and PIU was significantly associated with psychosomatic symptoms and life satisfaction. Effective measures are needed to prevent the spread of this problem and interventions to prevent the effects of PIU on psychosomatic symptoms and life satisfaction should be conducted as early as possible.